Estructura y dinámica de la población gallega entre 1950 y 2020. Entre la inercia y el pesimismo demográfico - Antía Pérez-Caramés (Cahiers de Civilisation Espagnole Contemporaine)
This article presents an analysis of the recent evolution of the Galician population, focusing both on aspects relating to its structure by sex and age, as well as its population dynamics. The period covered is between 1950 and 2020. Special attention is paid to the phenomenon of demographic ageing and also to the contribution of natural growth and migratory movements to population dynamics. Finally, a reflection is presented on the recent population policies implemented by the Galician government to address the demographic situation.